Synthesis and Antimicrobial/Cytotoxic Assessment of Ferrocenyl Oxazinanes, Oxazinan-2-ones, and Tetrahydropyrimidin-2-ones - Pejović, Anka; Danneels, Barbara; Desmet, Tom; Cham, Ba Thi; Van Nguyen, Tuyen; Radulović, Niko S.; Vukićević, Rastko D.; D’hooghe, Matthias (Synlett, 2015)
3-Arylamino-1-ferrocenylpropan-1-ones, prepared through aza-Michael addition of aromatic amines to 1-ferrocenylpropenone, were transformed into the corresponding 1,3-amino alcohols upon NaBH4-mediated carbonyl reduction. The latter amino alcohols were deployed as eligible substrates for the synthesis of a variety of ferrocene-containing heterocycles including 1,3-oxazinanes, 1,3-oxazinan-2-ones, and tetrahydropyrimidin-2-ones, which were subsequently evaluated for their antimicrobial and cytotoxic activities.
Keywords: ferrocenes; heterocycles; oxazinanes; oxazinan-2-ones; tetrahydropyrimidin-2-ones; cyclization; amino alcohols